Waste Sorting Machine Automatic of Organic and Inorganic Using Arduino Mega as Microcontroller : Implication for Environmental Sustainability - Bernadeta Wuri Harini; Benediktus Yudha Edy; Agustinus Surya Haryanto; Martanto Martanto; Petrus Setyo Prabowo; Ignatius Adi Prabowo (International Journal of Hydrological and Environmental for Sustainability, 2024)
Increasing waste production worldwide has become a serious environmental and social problem. Waste thrown into traditional landfills can pollute land and water, cause public health problems, and produce greenhouse gas emissions.  To overcome the issues above, in this research, a waste sorting machine will be designed that can sort organic and inorganic waste. This sorting is done automatically, a person only needs to put the waste into the machine, and then the waste will be separated according to its category.  The organic and inorganic waste sorting system consists of 5 sub-systems.  They are metal waste, glass waste, dry waste, plastic waste, and wet waste sorting.  The results of this study can produce a success rate of 66.7% in detecting the occupancy of the trash bin, 70% in sorting metal waste, and 44.4% in sorting glass waste.  The success rate in sorting wet waste is 40%, while in sorting plastic waste is 70%, and in dry waste is 90%.